A critical review of in vitro research methodologies used to study mineralization in human dental pulp cell cultures. (4th February 2022) - Arora, Shelly; Cooper, Paul R.; Ratnayake, Jithendra T.; Friedlander, Lara T.; Rizwan, Shakila B.; Seo, Benedict; Hussaini, Haizal M.
Abstract: Background: The pulp contains a resident population of stem cells which can be stimulated to differentiate in order to repair the tooth by generating a mineralized extracellular matrix. Over recent decades there has been considerable interest in utilizing in vitro cell culture models to study dentinogenesis, with the aim of developing regenerative endodontic procedures, particularly where some vital pulp tissue remains. Objectives: The purpose of this review is to provide a structured oversight of in vitro research methodologies which have been used to study human pulp mineralization processes. Method: The literature was screened in the PubMed database up to March 2021 to identify manuscripts reporting the use of human dental pulp cells to study mineralization. The dataset identified 343 publications initially which were further screened and consequently 166 studies were identified and it was methodologically mined for information on: i) study purpose, ii) source and characterization of cells, iii) mineralizing supplements and concentrations, and iv) assays and markers used to characterize mineralization and differentiation, and the data was used to write this narrative review. Results: Most published studies aimed at characterizing new biological stimulants for mineralization as well as determining the effect of scaffolds and dental (bio)materials. In general, pulp cells were isolated by enzymatic digestion, although the pulp explant technique was also common. For enzymatic digestion, a range of enzymes and concentrations were utilized, although collagenase type I and dispase were the most frequent. Isolated cells were not routinely characterized using either fluorescence‐activated cell sorting (FACS) and magnetic‐activated cell sorting (MACS) approaches and there was little consistency in terming cultures as dental pulp cells or dental pulp stem cells. A combination of media supplements, at a range of concentrations, of dexamethasone, ascorbic acid and beta‐glycerophosphate, were frequently applied as the basis for the experimental conditions. Alizarin Red S (ARS) staining was the method of choice for assessment of mineralization at 21‐days. Alkaline phosphatase assay was relatively frequently applied, solely or in combination with ARS staining. Further assessment of differentiation status was performed using transcript or protein markers, with dentine sialophosphoprotein (DSPP), osteocalcin and dentine matrix protein‐1 (DMP ‐1), the most frequent. Discussion: While this review highlights variability among experimental approaches, it does however identify a consensus experimental approach. Conclusion: Standardization of experimental conditions and sustained research will significantly benefit endodontic patient outcomes in the future.